Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d2ra06510j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of carbon black/silicone rubber composites with large-area-homogeneous-low electrical-resistance used as electroplating matrix

Abstract: Carbon black/silicone rubber composites with large-area-homogeneous-low electrical-resistance used as electroplating matrix and its fine electro-deposited Ni layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The findings show that the CB has a mitigating effect on oil-induced deterioration in LSR. However, as the CB content increased, the swelling ratio decreased, and it was observed that the swelling ratio increased slightly when 3 wt% of CB was added, which is presumed to be due to the agglomeration of the CB [38,39]. Furthermore, it was verified that the variation in swelling rate, dependent on the CB content, becomes more pronounced at elevated temperatures compared to room temperature.…”
Section: Swelling Characteristicsmentioning
confidence: 90%
See 1 more Smart Citation
“…The findings show that the CB has a mitigating effect on oil-induced deterioration in LSR. However, as the CB content increased, the swelling ratio decreased, and it was observed that the swelling ratio increased slightly when 3 wt% of CB was added, which is presumed to be due to the agglomeration of the CB [38,39]. Furthermore, it was verified that the variation in swelling rate, dependent on the CB content, becomes more pronounced at elevated temperatures compared to room temperature.…”
Section: Swelling Characteristicsmentioning
confidence: 90%
“…This accounts for the slight increase in the swelling ratio observed in the CB content of 3 wt%, as mentioned in Section 3.2. Consequently, in the CB/LSR tensile test shown in Figure 4b, the tensile strength increased with the rising CB content but experienced a slight decrease at 3 wt%, which was attributed to the observed agglomeration [38,39]. pared to the specimens with CB content of 1 wt% and 2 wt%, and some agglomeration was also observed.…”
Section: Morphological and Surface Characterizationmentioning
confidence: 93%
“…The use of various fillers in SR has gained significant attention for their ability to enhance the composite's desired properties 17 . Different fillers, such as carbon black, 18 silica, and metal oxides, 19 offer distinct advantages depending on the desired characteristics of the final product. Carbon black, a commonly used filler, enhances the properties of SR by improving tensile strength, tear resistance, and abrasion resistance 20 .…”
Section: Introductionmentioning
confidence: 99%
“…This typically involves adding more fillers to establish a continuous conductive network within the polymer, a crucial step for achieving optimal electrical conductivity. [31][32][33][34][35][36] However, a major obstacle lies in attaining uniform dispersion when blending conductive fillers directly into polymer substrates through physical blending, thereby restricting the practicality of this approach. 37 In order to enhance the dispersibility of conductive fillers in a polymer matrix, the functionalization method is commonly employed.…”
Section: Introductionmentioning
confidence: 99%